Utilizing Storytelling As A Persuasive Communication Technique In The Branding Of HMNS Perfume Products - Fani Agung Mulyani (LONTAR: Jurnal Ilmu Komunikasi, 2024)
In the competitive marketing sector, companies are realizing more and more how important narrative is as a means of developing close emotional relationships with customers. The effective incorporation of story into the branding strategy of HMNS, an Indonesian-based newly launched perfume brand, is investigated in this paper. With an eye toward stories that highlight the sources, inspirations, and creative techniques behind every perfume variation, HMNS purposefully uses storytelling to set its products apart in a crowded industry. Through a variety of digital channels including social media, the official website, and interactive marketing HMNS successfully shares emotionally powerful narratives to its audience. This study method consists on a case study, content analysis of HMNS marketing initiatives, and customer interviews to evaluate the effectiveness of narrative in increasing emotional appeal and client loyalty. The results suggest that encouraging customer engagement and developing strong emotional connections which in turn foster brand loyalty depending on narrative and are thus rather important. Well crafted tales appeal to consumers' individual experiences and ambitions, therefore encouraging inclusivity and a strong affinity for the HMNS brand. This research provides important new perspectives on how businesses could use story methods to create strong and long-lasting relationships with their consumers. It achieves this by looking at how consumer impressions and behavior change depending on narrative. HMNS's effective use of narrative highlights its ability to be a fascinating branding tool in the contemporary marketing scene. Keyword: Storytelling, Persuasive Communication, Branding, Perfume, HMNS